Exploring the supremacy of microvascular coupling devices for arterial anastomosis in terms of added expeditiousness, safety concerns: A systematic review - Ajit Kumar Vishwakarma; Naresh Kumar Sharma; Neeraj Kumar Dhiman; Shankar Singh; Chandresh Jaiswara; Sadhana Swaraj (Journal of Oral Biology and Craniofacial Research)
Background: Arterial anastomoses are still most commonly performed using orthodox hand sewing technique. Various rationale such as non-pliable, atherosclerotic, thick-walled or irradiated vessels limit the competency of coupler devices for arterial micro-anastomosis. Microvascular coupling devices (MCD) are well known for venous anastomoses but arterial MCD have relatively been less navigated in reported literatures. This review outlines the current applications, troubleshooting, safety and efficiency of arterial MCD in free flaps. Methods: Comprehensive search of electronic databases (PUBMED/MEDLINE) in accordance with PRISMA guideline was performed. Data were extracted and collected in four groups of standardised variables. Results: Out of a total of 263 identified articles, 38 studies were analysed and 16 amidst these were included in final data synthesis. Included studies contained a combined total of 2416 patients who went through 521 arterial and 2460 venous anastomoses using 3 M/Synovis coupling devices. Among all coupled arterial anastomoses, 407 were conducted in head and neck free tissue transfer and 114 were performed in breast reconstruction. The aggregate coupled arterial micro-anastomosis success rate reported was 90.01 % (469/521). Only 9.98 % (52 out of 521) manifested pooled incidence of troubleshooting, thrombosis or flap failure. Conclusion: Microsurgeons are resisting the frequent use of arterial coupling devices owing to inherent arterial characteristics, but with suitable vessel selection, arterial coupling may be a powerful tool and can be executed in safe, expeditious and reliable fashion. This study embellishes collaborative suggestions and troubleshooting issues related to arterial coupling, however further assessment would be required with controlled trials.